2022
DOI: 10.1021/acs.analchem.2c03518
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Microbubble Bursting Ionization Mass Spectrometry

Abstract: Aerosols generated by bubble bursting have been proved to promote the extraction of analytes and have ultrahigh electric fields at their water–air interfaces. This study presented a simple and efficient ionization method, carbon dioxide microbubble bursting ionization (CDMBI), without the presence of an exogenous electric field (namely, zero voltage), by simulating the interfacial chemistries of sea spray aerosols. In CDMBI, microbubbles are generated in situ by continuous input of carbon dioxide into an aqueo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 33 publications
3
4
0
Order By: Relevance
“…Carbon dioxide was selected as the BE gas because of its advantages over other gases. First, CO 2 has a superior response in MS, resulting in a higher sensitivity and lower LODs. , Additionally, CO 2 has a greater enrichment efficiency than the other gases, as demonstrated in Figure S3, which is consistent with the results of previous studies. , For a certain mass of PAHs, the smaller the diameter of the device, the greater the amount of aerosol adsorbed on the SPME coating. Moreover, increasing the diameter reduced the peak area (Figure S4).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Carbon dioxide was selected as the BE gas because of its advantages over other gases. First, CO 2 has a superior response in MS, resulting in a higher sensitivity and lower LODs. , Additionally, CO 2 has a greater enrichment efficiency than the other gases, as demonstrated in Figure S3, which is consistent with the results of previous studies. , For a certain mass of PAHs, the smaller the diameter of the device, the greater the amount of aerosol adsorbed on the SPME coating. Moreover, increasing the diameter reduced the peak area (Figure S4).…”
Section: Resultssupporting
confidence: 92%
“…21,22 Additionally, CO 2 has a greater enrichment efficiency than the other gases, as demonstrated in Figure S3, which is consistent with the results of previous studies. 21,22 For a certain mass of PAHs, the smaller the diameter of the device, the greater the amount of aerosol adsorbed on the SPME coating. Moreover, increasing the diameter reduced the peak area (Figure S4).…”
Section: Be-spme-gc−ms and Be-cntpsi-ms Proceduressupporting
confidence: 91%
See 1 more Smart Citation
“…[16][17][18] These differences arise due to the high specific surface area of the gas/liquid interface, which can significantly accelerate chemical reactions. 19,20 A strong electric field and high reactant concentrations at the droplet interface further contribute to the acceleration of these reactions. [21][22][23] Previous research has demonstrated the feasibility of promoting amine reactions with carbon dioxide (CO 2 ) through electrospray ionization (ESI) 24 and using NH 4 HCO 3 as a CO 2 source.…”
mentioning
confidence: 99%
“…Our previous bubble bursting studies have demonstrated the generation of high electric fields similar to those observed in ESI mechanisms. 20 However, the requirement for non/low-toxicity in practical application settings led us to explore the potential application of bubble bursting in the spontaneous reaction between amines in EtOH and CS 2 in the air, as depicted in our proposed application scenario (Fig. 4a).…”
mentioning
confidence: 99%